2017
DOI: 10.3390/ijerph14030325
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Psychiatric Services Providing an Alternative to Full-Time Hospitalization Is Associated with Shorter Length of Stay in French Public Psychiatry

Abstract: International recommendations for mental health care have advocated for a reduction in the length of stay (LOS) in full-time hospitalization and the development of alternatives to full-time hospitalizations (AFTH) could facilitate alignment with those recommendations. Our objective was therefore to assess whether the development of AFTH in French psychiatric sectors was associated with a reduction in the LOS in full-time hospitalization. Using data from the French national discharge database of psychiatric car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 60 publications
0
17
0
2
Order By: Relevance
“…This suggests that acute inpatient care, despite being intended for the small number of people with severe illness (Department of Health, 2017), could be lling these gaps, both for people in crisis, and for those who are no longer acute but still require a level of subacute residential support, particularly in the Australian regions where it comprises a larger part of the overall system . Length of stay in fulltime hospitalisation has been shown to correlate negatively with the development of alternatives to fulltime hospitalisation in the local context (Gandré et al, 2017). The lack of day care services in the Australian regions may also increase the need for inpatient care, as availability of day care services may play a role in reducing hospitalisation, maintaining health and promoting community participation through (i) the provision of alternatives to hospitalisation in the case of acute health related day services; and (ii) through assistance with skills training and education in the case of work related and structured day services.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that acute inpatient care, despite being intended for the small number of people with severe illness (Department of Health, 2017), could be lling these gaps, both for people in crisis, and for those who are no longer acute but still require a level of subacute residential support, particularly in the Australian regions where it comprises a larger part of the overall system . Length of stay in fulltime hospitalisation has been shown to correlate negatively with the development of alternatives to fulltime hospitalisation in the local context (Gandré et al, 2017). The lack of day care services in the Australian regions may also increase the need for inpatient care, as availability of day care services may play a role in reducing hospitalisation, maintaining health and promoting community participation through (i) the provision of alternatives to hospitalisation in the case of acute health related day services; and (ii) through assistance with skills training and education in the case of work related and structured day services.…”
Section: Discussionmentioning
confidence: 99%
“…France, a study used the LOS for public-sector psychiatric facilities to investigate whether the development of alternatives to full-time hospitalization (such as ambulatory care, part-time hospitalization, and full-time outpatient care) may reduce the LOS [15]. They found a significant negative association and concluded that their study was the first to provide nation-wide evidence of the benefits of alternatives to full-time hospitalization in psychiatry.…”
Section: Comparison With the International Literaturementioning
confidence: 99%
“…Indeed, in many countries, the healthcare system is based on a combined architecture: non-hospital care based on general practitioners who can address patients to other healthcare professionals (e.g. nurses, physiotherapists, specialists doctors) and hospital-based care [14,15]. Non-hospital care represents the most significant primary care contributor in many countries, including developing countries [16,17], because it ensures an effective and generally faster service that covers the large majority of personal healthcare needs [18], and acts as the principal point of continuing care for patients [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Psychiatric hospitalisation is often long-term and justifiable based on the risks to oneself or others combined with a severe incapacity to provide proper self-care that is exacerbated by the absence or insufficiency of family and/or social support. Mental disorders that may require prolonged psychiatric hospitalisation include schizophrenia [11,12] and major depressive disorder (MDD) [13] because of the risks they pose to affected patients and others. The time interval between the onset of the disorder (often unclear) and the initiation of appropriate treatment can be very long.…”
Section: Introductionmentioning
confidence: 99%